Scientometric analysis of computational calculations on hydrogen adsorption - D.A. Torres-Ceron; S. Amaya-Roncancio; F. Fuentes-Gandara; E. Restrepo-Parra; L. Bohorquez-Santiago; J.P. Velasquez-Tamayo (Global Journal of Environmental Science and Management)
The rapid industrialization has driven economic growth and population increase, but it has also led to significant environmental issues and energy shortages. In order to overcome these challenges and shift towards a carbon-neutral energy system, it is vital to investigate clean energy alternatives and lessen the reliance on fossil fuels. Among these alternatives, hydrogen stands out as a leading candidate due to its energy density and environmental affinity, being both abundant and renewable.  This study presents a comprehensive overview of the annual scientific production in the field of hydrogen adsorption and storage, categorized by country and authorship with the aim of assessing its evolution, thematic development, and global collaboration pattern. The present research was conducted in the databases Web of Science and Scopus from 2000 to 2022, using a pre-determined set of keywords related to hydrogen adsorption, storage, and density functional theory. The retrieved data were analysed with the Bibliometrix package in RStudio to evaluate publication trends, research evolution across three distinct periods and global collaboration networks. The present study involved the identification of 2183 documents, which were then screened and categorized by relevance in relation with hydrogen storage. In the present work, 881 articles were assessed for eligibility, identifying 60 key studies through degree and PageRank metrics, the evolution of research is delved into throughout three key stages. The three distinct periods identified were: the initial stage (2000-2008) which was marked by fundamental work on ionic liquids and hydrogen storage. The intermediate stage (2009-2015) witnesses an increase in scientific production, addressing fundamental principles and methodologies with a focus on metal-organic frameworks. The current stage (2016-2022) reflects maximum productivity and shows cutting-edge studies on nanotubes and electrocatalysts for the efficient evolution of hydrogen. The study explores global collaboration networks between countries and identifies influential authors and leading journals in the field. By the identification of the key trends, this study highlights the emergence of novel materials and technologies that are reshaping the hydrogen storage landscape. These advancements suggest potential pathways for future research and innovation, ultimately contributing to the development of sustainable energy solutions.  This bibliometric analysis provides valuable insights into the trends, contributions, and collaborative dynamics shaping the of hydrogen adsorption and storage research landscape.